The paper town – a movable book about paperless and digitisation - Dou, Meihuan (Nanyang Technological University, 2022)
The Paper Town is a fictional narrative presented in the form of a book. It was inspired by the contemporary technological turmoil, specifically the invention of LED screens, which could now overtake almost everything paper can do. This book titled "The Last of The Paper Town" was set to be the last physical book remaining after the town had fully digitized itself. It chronicles the only surviving analogue information of a town that is disappearing. The storyline circulates around a town that was once flourished by paper production getting intercepted and eventually completely disrupted by the rise of screens. The transitions within and gradual downfall of The Paper Town is used as a direct metaphor for the process of digitization, and the ‘paperless’ movement that we all experience around us. This book seeks to not only portray the fragility of paper as a material and medium of expression, but also challenge the extent we are willing to invite technology into our daily lives. This book presents itself as a eulogy for the diminishing presence of paper in daily lives.